Effectiveness of Common Beans Protein Extract (Phaseolus Vulgaris) as a Natural Coagulant in Purification of Portable Water. - Mushabe, Hillary (Kabale University, 2023)
Coagulation and flocculation are the commonest methods used for removal of turbidity from water. Of late, many researchers have focused on the investigation of natural coagulants for this purpose. In this study, the application of extracts from common bean seeds (Phaseolus Vulgaris) as natural coagulants during purification of drinking water was investigated. One sample of water was used in the experiments. The water Sample was collected was collected in calm weather conditions. Natural coagulants were extracted from crushed dry bean seeds by adding 5g of the bean powder into 1000mL of distilled water. The suspension was stirred for 45 minutes in a stirrer at room temperature and filtered using filter paper and the filtrate obtained was used to prepare coagulant doses during the experiments. Jar tests were conducted with different doses of the coagulant. After sedimentation, coagulation activity was determined by turbidity and colour measurements, results obtained showed that the highest coagulation activity of the natural coagulants from common beans was achieved at 66% and 54% turbidity and colour removal respectively with applied dose of 0.3 mg/L. The conducted experiments confirmed positive coagulation properties of these extracts and therefore, it can be concluded that they have a great potential as natural coagulants.